Biochemical and biological characterization of the Hypanus americanus mucus: A perspective on stingray immunity and toxins. Issue 93 (October 2019) - Coelho, Guilherme Rabelo; Neto, Pedro Prezotto; Barbosa, Fernanda Cortinhas; Dos Santos, Rafael Silva; Brigatte, Patrícia; Spencer, Patrick Jack; Sampaio, Sandra Coccuzzo; D'Amélio, Fernanda; Pimenta, Daniel Carvalho; Sciani, Juliana Mozer
Abstract: Stingrays skin secretions are largely studied due to the human envenoming medical relevance of the sting puncture that evolves to inflammatory events, including necrosis. Such toxic effects can be correlated to the biochemical composition of the sting mucus, according to the literature. Fish skin plays important biological roles, such as the control of the osmotic pressure gradient, protection against mechanical forces and microorganism infections. The mucus, on the other hand, is a rich and complex fluid, acting on swimming, nutrition and the innate immune system. The elasmobranch's epidermis is a tissue composed mainly by mucus secretory cells, and marine stingrays have already been described to present secretory glands spread throughout the body. Little is known about the biochemical composition of the stingray mucus, but recent studies have corroborated the importance of mucus in the envenomation process. Aiming to assess the mucus composition, a new non-invasive mucus collection method was developed that focused on peptides and proteins, and biological assays were performed to analyze the toxic and immune activities of the Hypanus americanus mucus. Pathophysiological characterization showed the presence of peptidases on the mucus, as well as the induction of edema and leukocyte recruitment in mice. The fractionated mucus improved phagocytosis on macrophages and showed antimicrobial activity against T. rubrumç. neoformans and C. albicans in vitro . The proteomic analyses showed the presence of immune-related proteins like actin, histones, hemoglobin, and ribosomal proteins. This protein pattern is similar to those reported for other fish mucus and stingray venoms. This is the first report depicting the Hypanus stingray mucus composition, highlighting its biochemical composition and importance for the stingray immune system and the possible role on the envenomation process. Highlights: A method was developed for the attainment of stingray mucus. The mucus induces edema and leukocyte recruitment in mice. The mucus shows antinfungal and immunomodulatory activities. The mucus protein profile is similar to the previously described venom profiles.